Scrubbers microorganisms associated with cattails (Typha latifolia) in the treatment ofwaste water - Maxe Malca, María Raquel (2016)
This work was carried out in order to identify the low level of environmental awareness in which children in fourth grade of primary education are, having a population of 202 students and taking as sample to fourth grade "C" with 32 children. This research was conducted at the Educational Institution No. 11014 "Inmaculada Concepción" - Chiclayo. For this problem, an instrument was applied as a pretest called checklist that produced qualitatively that 56% of students are at a low level, while 25% are at a medium level and 19% are at a high level; 56% on the ethical level and 34% on the social leve!; then a training workshop was put into practice with severa! activities and strategies that were intended to improve or change students' attitudes towards their environment, contributing to their comprehensive training and achieving see positive results demonstrated in the post test.